A-Kinase Anchor Protein 12 Is Required for Oligodendrocyte Differentiation in Adult White Matter. (22nd January 2018) - Maki, Takakuni; Choi, Yoon Kyung; Miyamoto, Nobukazu; Shindo, Akihiro; Liang, Anna C.; Ahn, Bum Ju; Mandeville, Emiri T.; Kaji, Seiji; Itoh, Kanako; Seo, Ji Hae; Gelman, Irwin H.; Lok, Josephine; et al.
Abstract : Oligodendrocyte precursor cells (OPCs) give rise to oligodendrocytes in cerebral white matter. However, the underlying mechanisms that regulate this process remain to be fully defined, especially in adult brains. Recently, it has been suggested that signaling via A-kinase anchor protein 12 (AKAP12), a scaffolding protein that associates with intracellular molecules such as protein kinase A, may be involved in Schwann cell homeostasis and peripheral myelination. Here, we asked whether AKAP12 also regulates the mechanisms of myelination in the CNS. AKAP12 knockout mice were compared against wild-type (WT) mice in a series of neurochemical and behavioral assays. Compared with WTs, 2-months old AKAP12 knockout mice exhibited loss of myelin in white matter of the corpus callosum, along with perturbations in working memory as measured by a standard Y-maze test. Unexpectedly, very few OPCs expressed AKAP12 in the corpus callosum region. Instead, pericytes appeared to be one of the major AKAP12-expressing cells. In a cell culture model system, conditioned culture media from normal pericytes promoted in-vitro OPC maturation. However, conditioned media from AKAP12-deficient pericytes did not support the OPC function. These findings suggest that AKAP12 signaling in pericytes may be required for OPC-to-oligodendrocyte renewal to maintain the white matter homeostasis in adult brain. Abstract : In adult white matter, AKAP12 in pericytes regulates the production of growth factors, which promote oligodendrocyte differentiation for maintaining white matter homeostasis.